2020
DOI: 10.1136/bmjgh-2019-001987
|View full text |Cite
|
Sign up to set email alerts
|

Arts-based approaches to promoting health in sub-Saharan Africa: a scoping review

Abstract: IntroductionArts-based approaches to health promotion have been used widely across sub-Saharan Africa (SSA), particularly in public health responses to HIV/AIDS. Such approaches draw on deep-rooted historical traditions of indigenous groups in combination with imported traditions which emerged from colonial engagement. To date, no review has sought to map the locations, health issues, art forms and methods documented by researchers using arts-based approaches in SSA.MethodsUsing scoping review methodology, 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 134 publications
1
40
0
1
Order By: Relevance
“…Generally, edutainment health interventions are complementary to traditional public health interventions ( 18 ). Several studies have reported how songs and music can be used as a means of education and increasing awareness in public health context and clinical experience ( 12 , 19 – 21 , 50 ). Thus, the use of music to influence knowledge, attitudes and behaviors toward infectious diseases like COVID-19 is not a new phenomenon in Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, edutainment health interventions are complementary to traditional public health interventions ( 18 ). Several studies have reported how songs and music can be used as a means of education and increasing awareness in public health context and clinical experience ( 12 , 19 – 21 , 50 ). Thus, the use of music to influence knowledge, attitudes and behaviors toward infectious diseases like COVID-19 is not a new phenomenon in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…It was aimed at de-stigmatizing HIV/AIDS, encouraging compassionate care and support for people living with HIV/AIDS, and encouraging citizens to adopt safe sex behavior ( 25 ). Also, various studies document how popular musicians were commissioned by organizations such as WHO and UNICEF in 2014–2016 to compose prevention songs as a response to the Ebola outbreak in Liberia and other parts of Africa ( 21 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Communication material can take the form of news articles and social media posts; community meetings, newspaper articles, videos or short films, documentaries, podcasts, infographics, etc. Art-based approaches, such as theatre, music, visual arts, storytelling and film 67 are especially useful to reach and engage large numbers of people. Study findings need to be communicated neutrally and impartially, and where necessary conflicts of interest need to be clarified/declared.…”
Section: Put In Place Quality Control Mechanisms To Ensure That Data mentioning
confidence: 99%
“…In sub-Saharan Africa, use of artistic forms [ 23 – 26 ] to engage with communities is the most commonly reported strategy. According to Bunn and colleagues [ 24 ], 17 different categories of art forms are widely used in sub-Saharan Africa with theatre, music and song, TV/radio, visual arts and storytelling being among the top 5.…”
Section: Introductionmentioning
confidence: 99%